Physics of atoms, molecules, solids and nuclei - Jain, Vimal Kumar (New Delhi: Narosa Publishing House, 2017)
b
Includes Bibliography and index
Keywords: Atomic physics -- Molecular physics -- Solid state physics -- Nuclear physics